Comparative Efficacy of Alendronate upon Vertebral Bone Mineral Density and Fracture Rates in East Asians Versus Non-East Asians with Postmenopausal Osteoporosis: A Systematic Review and Meta-Analysis - Wang, Yexin; Jia, Gongwei; Song, Jin; Kong, Xiangqing; Zhang, Weihong; Meng, Chunyang (Hormone and Metabolic Research, 2018)
Bisphosphonates, such as alendronate, have become the most widely used and effective anti-resorptive therapy for postmenopausal osteoporosis. Previous genetic studies suggest that ethnicity may drive differing responses to bisphosphonate therapy in East Asians and non-East Asians. Therefore, the aim of this study was to comparatively evaluate the efficacy of alendronate upon lumbar spinal BMD and vertebral fracture rates in East Asians and non-East Asians with postmenopausal osteoporosis. MEDLINE, EMBASE, and Cochrane CENTRAL were searched for relevant randomized controlled trials (RCTs) comparing the efficacy of alendronate versus placebo (or calcium/mineral and/or Vitamin D or hormone replacement therapy) in primary postmenopausal osteoporotic women. We calculated the weighted mean differences (WMDs) for lumbar spinal BMD and the risk ratios (RRs) for vertebral fracture risk along with their respective 95% confidence intervals (CIs). From an initial set of 445 non-duplicate records, 13 full-text articles were finally included in this meta-analysis consisting of four East Asian RCTs and nine non-East Asian RCTs. Alendronate therapy displayed significant effects in improving lumbar spinal BMD in both East Asians [WMD (95% CI)=5.30 (0.32–10.29), p=0.037] and non-East Asians [WMD (95% CI)=5.73 (3.61–7.85), p=0.000]. Alendronate therapy did not display significant effects upon vertebral fracture risk in East Asians [RR (95% CI)=0.41 (0.06–2.73), p=0.358] but did display a significant effect upon lowering vertebral fracture risk in non-East Asians [RR (95% CI)=0.55 (0.42–0.72), p=0.000]. These findings suggest that ethnicity may affect the efficacy of bisphosphonate therapy in postmenopausal osteoporotic women.
Keywords: bisphosphonate; alendronate; postmenopausal; osteoporosis; BMD; vertebral fracture; Asian